Chasing Cysteine Oxidative Modifications: Proteomic Tools for Characterizing Cysteine Redox Status - Murray, Christopher I.; Van Eyk, Jennifer E. (Circulation. Cardiovascular genetics, 2012)
Redox-proteomics involves the large scale analysis of oxidative protein post-translational modifications. In particular, cysteine residues have become the subject of intensifying research interest because of their redox-reactive thiol side chain. Certain reactive cysteine residues can function as redox-switches, which sense changes in the local redox-environment by flipping between the reduced and oxidized state. Depending on the reactive oxygen or nitrogen species, cysteine residues can receive one of several oxidative modifications, each with the potential to confer a functional effect. Modification of these redox-switches has been found to play an important role in oxidative-signaling in the cardiovascular system and elsewhere. Due to the labile and dynamic nature of these modifications, several targeted approaches have been developed to enrich, identify and characterize the status of these critical residues. Here, we review the various proteomic strategies and limitations for the large scale analysis of the different oxidative cysteine modifications.